Is there any putative mediatory role of inflammatory markers on the association between ultra-processed foods and resting metabolic rate? - Bahrampour, Niki; Shiraseb, Farideh; Noori, Sahar; Clark, Cain C. T.; Mirzaei, Khadijeh (Frontiers in Nutrition, 2022)
Resting metabolic rate (RMR) represents the largest component of total daily energy expenditure. The sale of ultra-processed foods (UPF) is increasing globally; however, UPF can have many adverse effects, including increasing inflammatory markers and altering RMR. This cross-sectional study included 285 healthy overweight and obese women. Anthropometric measurements were evaluated with bioelectrical an impedance analyzer InBody 770 scanner. High sensitive C reactive protein (hs-CRP), plasminogen activator-1 (PAI-1), Monocyte chemoattractant protein (MCP-1), and interleukin-1 beta (IL-1ꞵ) blood levels were measured after 12 hours fasting. Indirect calorimetry was used to evaluate RMR with the Weir equation, and RMR deviation (RMR estimated – RMR actual), RMR per body mass index (BMI), and free fat mass (FFM) were estimated. A validated food frequency questionnaire (FFQ) was used, and seven groups of UPF were extracted based on the NOVA method. A negative association between RMR (β= -0.159, 95% confidence interval (CI): -0.471, -0.052, P= 0.044) and RMR per BMI (β= -0.014, 95% CI: -0.025, -0.006, P= 0.036), RMR per FFM (β= -0.241, 95% CI: -0.006, -0.000, P= 0.041) with NOVA score was observed after adjusting for confounders. This association disappeared after inclusion of each inflammatory marker. All of the markers may inversely mediate the relationship between mentioned variables and NOVA score. Hs-CRP and MCP-1 also had a negative effect on the relationship between NOVA score and RMR deviation. Finally, UPFs intake are likely related with RMR, mediated through changes in the production of hs-CRP, PAI-1, MCP-1, and IL-1ꞵ.